English and Uzbek News Headlines: Stylistic and Cultural Variations - Begaliyeva Sohiba Sobir qizi (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2026)
This article provides an in-depth comparative analysis of stylistic, lexical, syntactic, and pragmatic features of news headlines in English and Uzbek media discourse. Drawing on a qualitative corpus of thirty paired headlines from leading English-language outlets (BBC, CNN) and Uzbek-language platforms (Kun.uz, UzA) published between January and March 2026, the study identifies systematic differences rooted in cultural communication patterns. The findings demonstrate that English headlines prioritize brevity, ellipsis, emotional expressiveness, and reader engagement strategies, reflecting individualistic and market-driven media traditions. Uzbek headlines, by contrast, exhibit syntactic completeness, lexical neutrality, politeness markers, and contextual transparency, which align with collectivist cultural norms and institutional communication practices. The study applies Hofstede’s cultural dimensions theory as an analytical framework and contributes to the fields of media linguistics, intercultural communication, and translation studies. Practical implications are discussed for journalists, translators, and educators working in multilingual environments, particularly within Central Asia.